2019
DOI: 10.3390/app9102017
|View full text |Cite
|
Sign up to set email alerts
|

Data Interpretation Technology of GPR Survey Based on Variational Mode Decomposition

Abstract: Data interpretation is the crucial scientific component that influences the inspection accuracy of ground penetrating radar (GPR). Developing algorithms for interpreting GPR data is a research focus of increasing interest. The problem of algorithms for interpreting GPR data is unresolved. To this end, this study proposes a sophisticated algorithm for interpreting GPR data with the aim of improving the inspection resolution. The algorithm is formulated by integrating variational mode decomposition (VMD) and Hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…λ is Lagrange multipliers. A detailed description can be found in the related literature [11][12][13][14].…”
Section: A Brief Review Of the Vmd Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…λ is Lagrange multipliers. A detailed description can be found in the related literature [11][12][13][14].…”
Section: A Brief Review Of the Vmd Algorithmmentioning
confidence: 99%
“…In this regard, Zhang et al applied the VMD method to GPR data processing, and both experimental and field-measured data showed that VMD−derived IMFs are sparser and match better with the signal's intrinsic properties than those derived from EMD denoising processing [12]. Xu and Lei also applied the VMD method to GPR signals with non-stationary characteristics and found that the VMD method was effective in removing noise from the GPR signal in a strong noise background and VMD was better at overcoming the influences of mode aliasing and endpoint effects compared to the traditional methods like EMD and EEMD [13]. He et al proposed a novel joint time−frequency analysis (JTFA) method based on the VMD for GPR data processing and verified that VMD outperforms the EMD, EEMD, and CEEMD in signal decomposition robustness and anti−noise ability by the synthetic signals, and the real−world field data [14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistics of the Munich Re Group disaster database, in the six years from 2013 to 2018, 36,200 deaths were caused by global hydrological events with an economic loss of 213 billion USD, of which catastrophic hydrologic events accounted for about 56% [6]. In all catastrophic hydrological events, storm surges and huge waves caused by typhoons have severely threatened the survival and development of humankind with their frequent occurrences and formidable destructive power [7][8][9]. Establishing projects, such as wave and flood prevention seawalls, is an effective way to prevent the destruction of offshore constructions caused by typhoons (hurricanes) from marine dynamic environmental factors (wind, waves, etc.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Recently, the variational mode decomposition (VMD), which encompasses multiple adaptive Wiener filter groups, has been widely used to process GPR signal, because it showed a good robustness in overcoming the disadvantages of mode aliasing, small end effects, and pseudocomponents when compared to other traditional TF analysis algorithms for GPR [13,14]. This innovative VMD method also has a solid theoretical foundation in decomposing the adaptive and quasiorthogonal signals [15].…”
Section: Introductionmentioning
confidence: 99%